Audit Strategies and Multiple Fraud Opportunities of Misreporting and Defalcation* - Patterson, Evelyn; Noel, James (Contemporary Accounting Research, 2003)
Abstract We examine how an auditor assesses the risk of fraud and formulates an audit plan when the auditee has the opportunity to commit various types of fraud. Unlike previous studies, the audi‐tee can misappropriate assets (defalcation), misreport financial information (fraudulent financial reporting), or misreport financial information in combination with defalcation. Our results identify four possible equilibria whose characteristics depend on the auditee's relative rewards and penalties from the various types of fraud, the cost of audit effort, and expectations about the auditee‐firm's performance. When the cost of audit effort is sufficiently small, fraud risk assessment depends on the auditee's rewards and penalties associated with each type of fraud, but not on the auditor's beliefs about firm performance. The auditor develops an audit plan that focuses on the type of fraud the auditee is most motivated to commit, and in turn, the audit plan deters all other types of fraud.